Assessment of Physical and Chemical Quality Standards for Water and Sanitation Disclosure Towards SDG 6: A Study in Wijimulyo, Nanggulan, Kulon Progo Regency - Kurniawan, Muhammad Prasetya; Wibowo, Setyawan Bekti; Hidayah, Nurulia; Santoso, Probo; Octaviani, Danis Syalwa; Larasati, Errika Anggraini; Rachman, Atika Yulia; Nurramdhana, Almaira Daffa; Mahardini Gunawan, Citra Aulia (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2024)
Collaboration between academics, educators, students, village civil servants, and the community is needed to implement Sustainable Development Goal (SDG) 6. It is related to clean water and sanitation in the context of training vocational teachers and students to provide it to the community. First, measurements were made of the water quality around the research area. Sixty-three water samples were drawn from each resident's home's water supply. A multi-parameter water quality checker was used to evaluate the samples, and then spatial data processing was used. A temperature of 24.1 C, turbidity of 0.4 NTU, conductivity of 0.4 mS/cm, pH 7.1, salinity of 0.2 ppt, DO of 5.9 mg/l, and TDS value of 267 mg/l were measured. These average results indicate that the water quality satisfies both Indonesian National Standard 3553:2015 and the water quality criteria set by the Minister of Health of the Republic of Indonesia Regulation No. 2 Year 2023. However, the results of tracking every sampling location show that several samples fall short of water quality requirements because of the high mineral content, weather, and other factors. Every school and community organization needs to run scenarios to raise awareness about water quality standards involving the government, non-governmental organizations, and the private sector to implement SDGs 6, such as stakeholder engagement, community enhancement, and policy and regulation.